RETRACTED: Chemical mechanisms of biogas production from wastewater algal biomass via cobalt-catalysed pyrolysis and methanogenic co-digestion - Ning Zuo; JinChao He; XueMei Tan (PLoS ONE, 2025)
Biogas energy derived from recycled algal biomass grown on wastewater could provide a sustainable pathway for a renewable future. This research investigates the chemical details of cobalt-catalysed pyrolysis integrated with methanogenic archaea co-anaerobic fermentation to improve biogas and methane generation from wastewater algae. Algal biomass (500 mL sample) was harvested from multiple locations at the Qinghe Wastewater Treatment Plant in Beijing, China. The algal species Chlorella vulgaris and Scenedesmus obliquus were identified. A 5% Co/Al₂O₃ catalyst was prepared by impregnating commercial alumina with a cobalt nitrate solution. Pyrolysis was conducted in a 500 mL fixed-bed reactor, and bio-oil and char yields were measured. Thermal degradation of biomass and by-products was analysed using thermogravimetric analysis (TGA). Microbial cultures of Methanosaeta concilii and Methanosarcina barkeri were used for anaerobic fermentation in 1 L batch biodigesters, with bio-oil as the carbon source. Biogas production kinetics were modelled using the modified Gompertz and Arrhenius equations. Statistical analyses were performed using GraphPad Prism version 10.2.0 and R version 4.03. The results demonstrated that biogas production in the experimental group was significantly higher across all temperatures. Maximum methane yield (Pmax) increased from 301.05 mL at 400°C to 436.71 mL at 800°C in the experimental group, compared to the control group. The rate constant (k) for biogas production also increased, reaching 0.20 mL/day at 800°C in the experimental group. CO₂ yield was higher in the control group at lower temperatures, while the integrated system consistently produced more biochar and biogas. The energy efficiency analysis revealed that the calorific value of biogas increased from 7.552 MJ at 400°C to 12.966 MJ at 800°C in the experimental group, with net energy gain decreasing as temperature increased. The mass balance showed that, during the pyrolysis stage, 100 g of biomass resulted in 35 g of biochar, 250 mL of biogas, and 50 g of bio-oil. In the anaerobic digestion stage, 155.47 g of biochar and 300 mL of biogas were produced. Kinetic model analysis showed that the activation energy for pyrolysis in the experimental group decreased from 145 kJ/mol at 400°C to 125 kJ/mol at 800°C, while the maximum methane yield in the Gompertz model increased from 405.026 mL at 400°C to 434.525 mL at 800°C in the experimental group. Thermogravimetric analysis (TGA) showed that biomass had 96.8% volatile matter, while biochar had 87.5% volatile matter and 12.5% ash content. BET surface area analysis of Co/Al₂O₃ biochar showed a surface area of 400 m²/g. Cobalt-catalysed pyrolysis and the subsequent anaerobic digestion process provide synergistic effects, leading to enhanced biogas yield while reducing the production time required.